Fiber membrane with poly (p-dioxanone) as base material and preparation method of fiber membrane

By using fiber membranes with polyptioxane as the substrate and electrospinning technology combining bioglass and nano cerium oxide, the problem of the lack of artificial dura substitutes to promote tissue reconstruction and rapid degradation is solved, and the effect of shortening the patient's recovery cycle and improving the repair effect is achieved.

CN119733109AActive Publication Date: 2025-04-01SICHUAN UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411791110.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-01
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In the prior art, artificial dura substitutes lack the ability to promote tissue reconstruction, positively regulate cells to achieve the ability to shorten the repair cycle, and their own degradation cycle is relatively long.

Method used

A fiber membrane with polyptioxane as the base material is used, and the preparation method includes mixing PPDO with organic solvent to prepare a PPDO solution, performing film laying and electrospinning treatment to form a bilayer structure fiber membrane. The fiber membrane is prepared by electrospinning technology, combining bioglass (BG) and nanocerium oxide (CNP) to promote cell growth and angiogenesis and achieve rapid degradation.

Benefits of technology

The rapid degradation and cytocompatibility of fiber membranes are achieved, the recovery cycle of patients is shortened, the effect of dura repair is improved, and the pain and recovery time of patients are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733109A_ABST
    Figure CN119733109A_ABST
Patent Text Reader

Abstract

The invention provides a fiber membrane with poly (p-dioxanone) as a base material and a preparation method of the fiber membrane, and relates to the technical field of engineering tissue materials. The fiber membrane with the poly (p-dioxanone) as the base material comprises an outer compact layer made of a PPDO material and an inner layer made of the PPDO material, wherein the inner layer is formed on the outer compact layer through electrostatic spinning; the preparation method comprises the following steps: S10, mixing PPDO with an organic solvent to prepare a PPDO solution a, paving the PPDO solution a for multiple times, and drying to prepare a PPDO substrate film; s20, mixing PPDO with an organic solvent to prepare a PPDO electrospinning solution c; s30, carrying out electrostatic spinning on the PPDO substrate membrane by using the electrospinning solution c to prepare a fiber membrane taking poly (p-dioxanone) as a base material; the intracranial cell behavior can be positively regulated and controlled, the degradation period is shortened, and the recovery process of a patient is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering tissue materials, in particular to a fiber membrane with polydioxanone as a substrate and a preparation method thereof. Background Art

[0002] Engineered tissue materials are biomaterials used in tissue engineering to construct or repair human tissues and organs. These materials can serve as scaffolds for cell growth, provide necessary structural support and biological signals, and promote cell attachment, proliferation, and differentiation.

[0003] Artificial Dura Mater is a fibrous membrane made of engineered tissue material that replaces the human meninges. It is used to repair defects in the dura mater or spinal meninges caused by craniocerebral and spinal cord injuries, tumors, and other craniocerebral diseases, to prevent serious complications such as cerebrospinal fluid leakage, intracranial infection, brain herniation, brain adhesions, and scars, so as to restore their integrity.

[0004] In cranial surgery, according to the requirements of neurosurgery, the ideal dura mater repair material should be easy to operate, convenient for surgery, have high biocompatibility and suitable mechanical properties, promote the formation of new tissue at the injured site during degradation, reduce scar formation, and not adhere to surrounding tissue. To solve this problem, researchers have developed artificial dura maters of various materials, such as natural biomaterials, autologous and allogeneic transplant materials, and artificial materials. Compared with other materials, artificial materials have excellent biocompatibility, good mechanical properties, and have great advantages in antibacterial, storage, manufacturing and transportation. They are a very potential alternative material for dura mater. Designing new strategies for constructing artificial dura mater repair materials and realizing their antibacterial, anti-inflammatory and rapid reconstruction functions of the inner layer of tissue have great research significance and clinical application prospects for improving the efficacy of dura mater repair and improving the postoperative recovery of patients.

[0005] Problems with artificial dura mater substitutes in the prior art include: long repair cycle, poor biocompatibility, lack of ability to positively regulate cells, etc. Artificial polymer materials used for dura mater repair mainly include: polyglycolic acid (PGA), polyurethane (PU), polycaprolactone (PCL) and poly(lactic acid) (PLLA). In Japan, polyglycolic acid (PGA) patches have been approved as artificial substitutes for dura mater in clinical practice, but the results achieved in terms of efficacy are not satisfactory. A considerable number of clinical reports have shown that PGA patches have poor biocompatibility and adverse reactions after surgery, including granulation tissue formation, meningeal infection, etc. Polycaprolactone (PCL) and poly(lactic acid) (PLLA) are two artificial dura mater substitute materials approved for marketing by the US FDA. Compared with PGA, they have good biodegradability and biocompatibility, have been proven to prevent cerebrospinal fluid leakage, and combine with surrounding tissues to repair dura mater defects. No obvious infection occurred in clinical studies, but the degradation cycle is as long as more than half a year. In summary, the main problem with artificial dura mater substitutes made from current materials is that they lack the ability to promote tissue reconstruction and positively regulate cells to shorten the repair cycle, and their own degradation cycle is relatively long, which limits the recovery speed of patients using artificial dura mater and increases the burden on patients. Summary of the invention

[0006] The present invention aims to solve the problems in the prior art that tissue engineering material substitutes such as artificial dura mater lack the ability to promote tissue reconstruction and positively regulate cells to shorten the repair cycle, and their own degradation cycle is relatively long. The present invention provides two fiber membranes based on polydioxanone and a preparation method thereof, which can positively regulate intracranial cell behavior, promote tissue reconstruction, and quickly degrade, thereby shortening the patient's recovery cycle.

[0007] The technical solution adopted by the present invention is:

[0008] A method for preparing a fiber membrane with polydioxanone as a substrate comprises the following steps:

[0009] S10. Mixing PPDO and an organic solvent to prepare a PPDO solution a, using the PPDO solution a to lay a film multiple times, and drying to obtain a PPDO basement membrane;

[0010] S20. Preparing electrospinning solution c by mixing PPDO with an organic solvent;

[0011] S30. On the PPDO substrate membrane, electrospinning is performed using the electrospinning solution c to obtain a fiber membrane with polydioxanone as the substrate;

[0012] There is no fixed order between steps S10 and S20.

[0013] Further,

[0014] The S20 includes: preparing a PPDO solution b by mixing PPDO with an organic solvent, and adding a BG suspension to the PPDO solution b to prepare a PPDO electrospinning solution c.

[0015] Further,

[0016] The organic solvents used in S10 and S20 are both hexafluoroisopropanol, and the bubbles in the mixed PPDO solution a and PPDO solution b need to be removed.

[0017] Further,

[0018] The S10 specifically includes: mixing PPDO and hexafluoroisopropanol, sealing and avoiding light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution a; pouring the pure PPDO solution a into a glass dish three times at intervals, and applying it with a coater after each pouring to ensure that the surface is uniform; after three times of film laying, placing the mixture in a constant temperature vacuum drying oven and drying in a vacuum environment to obtain a PPDO basement membrane.

[0019] Further,

[0020] The S20 specifically includes: mixing PPDO with hexafluoroisopropanol, sealing and protecting from light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution b; mixing excess BG powder with deionized water, ultrasonically shaking to mix them evenly, centrifuging to obtain the supernatant, and then taking a certain amount of BG suspension and adding it to the pure PPDO solution b to obtain a PPDO electrospinning solution c.

[0021] Further,

[0022] The S30 specifically includes: adding the electrospinning solution c into an electrospinning liquid syringe to remove bubbles; performing electrospinning multiple times using an electrospinning instrument to obtain a fiber membrane with polydioxanone as a substrate;

[0023] Among them, the spinning voltage is controlled at 10~30kV, the syringe propulsion speed is controlled at 0.1~5mL / h, the distance between the electrospinning needle and the receiver is controlled at 50~150mm, and the left and right movement speed of the needle is suitable for being controlled at 25~100mm / sec, and the roller receiver speed is controlled at 0~5000 rpm.

[0024] Further,

[0025] The PPDO concentration of the electrospinning solution c prepared in S20 is 0.06 g / mL~0.10 g / mL.

[0026] Further,

[0027] The silicon concentration of the electrospinning solution c prepared in S20 is 0.5 mg / L to 50 mg / L.

[0028] A fiber membrane with polydioxanone as a substrate is prepared by the above-mentioned preparation method, comprising:

[0029] An outer dense layer of PPDO material; and

[0030] An inner layer of PPDO material is formed by electrospinning on the outer dense layer.

[0031] Another method for preparing a fiber membrane using polydioxanone as a substrate comprises the following steps:

[0032] S10. Mixing PPDO and an organic solvent to prepare a PPDO solution a, using the PPDO solution a to lay a film multiple times, and drying to obtain a PPDO basement membrane;

[0033] S20. Mixing PPDO and an organic solvent to prepare a PPDO solution b, and adding a BG suspension to the PPDO solution b to prepare a PPDO electrospinning solution c;

[0034] S22. CNPs were mixed with an organic solvent and poloxamer was added to prepare an electrospinning solution d;

[0035] S30. On the PPDO substrate membrane, electrospinning solution c and electrospinning solution d are used to simultaneously perform electrospinning to obtain a fiber membrane based on polydioxanone;

[0036] There is no fixed order among the steps S10, S20 and S22.

[0037] Further,

[0038] The organic solvents used in S10, S20 and S22 are all hexafluoroisopropanol, and the bubbles in the mixed PPDO solution a and PPDO solution b need to be removed.

[0039] Further,

[0040] The S10 specifically includes: mixing PPDO and hexafluoroisopropanol, sealing and avoiding light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution a; pouring the pure PPDO solution a into a glass dish three times at intervals, and applying it with an applicator after each pouring to ensure that the surface is uniform; after three times of film laying, placing the mixture in a constant temperature vacuum drying oven and drying in a vacuum environment to obtain a PPDO basement membrane.

[0041] Further,

[0042] The S20 specifically includes: mixing PPDO with hexafluoroisopropanol, sealing and protecting from light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution b; mixing excess BG powder with deionized water, ultrasonically shaking to mix them evenly, centrifuging to obtain the supernatant, and then taking a certain amount of BG suspension and adding it to the pure PPDO solution b to obtain a PPDO electrospinning solution c.

[0043] Further,

[0044] The S22 specifically includes: mixing the CNPs group with hexafluoroisopropanol, sealing and protecting from light, and ultrasonically treating at room temperature to make the nano-cerium oxide uniformly dispersed in the hexafluoroisopropanol; adding poloxamer, sealing and protecting from light, and stirring at room temperature to make the poloxamer completely dissolved in the hexafluoroisopropanol, so as to prepare the electrospinning solution d.

[0045] Further,

[0046] The S30 specifically includes: using double-head synchronous electrospinning technology, the electrospinning solution c and the electrospinning solution d are synchronously injected using different syringes; and using an electrospinning instrument to perform multiple electrospinning to obtain a fiber membrane with polydioxanone as the substrate.

[0047] Further,

[0048] The preparation method of the CNPs group used in S22 comprises:

[0049] Place cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O) in a container, and add 1-octadecene, oleylamine and deionized water; place the container containing the weighed drugs in an oil bath, and continue to stir to completely dissolve cerium (III) nitrate hexahydrate in octadecene and oleylamine to form a brown-yellow liquid; then increase the temperature and continue to stir for 1.5-4 hours to obtain a reaction solution containing CNP nanoparticles;

[0050] The reaction solution was taken out from the container, cooled to room temperature, and then a large amount of a mixture of dichloromethane and ethanol was added to disperse and precipitate the CNP nanoparticles, and the mixture was allowed to stand for 24 to 48 hours; the precipitated liquid was centrifuged in a low-speed centrifuge for 5 to 30 minutes to obtain CNPs clusters.

[0051] Further,

[0052] The CNPs content in the electrospinning solution d prepared in S22 is 0.01%~0.1%.

[0053] A fiber membrane with polydioxanone as a substrate is prepared by the above-mentioned preparation method, comprising:

[0054] An outer dense layer of PPDO material; and

[0055] The inner layer of PPDO-poloxamer hydrogel incorporating BG and CNP is formed by electrospinning on the outer dense layer.

[0056] The beneficial effects of the present invention are:

[0057] 1. The fiber membrane of the present invention uses PPDO as the outer dense layer to prevent the penetration of intracranial cerebrospinal fluid. On the other hand, PPDO has good cell compatibility and degradable properties, so as to improve the cell compatibility and rapid degradation performance of the fiber membrane, thereby solving the problem that the fiber membrane substitute in the prior art has poor cell compatibility and a long degradation cycle.

[0058] 2. A fiber membrane of the present invention uses PPDO as an outer dense layer to prevent intracranial cerebrospinal fluid from penetrating; and a certain concentration of BG is added to PPDO to prepare the inner layer through electrospinning technology. Since electrospinning can produce a structure similar to the extracellular matrix (ECM), and PPDO has good cell compatibility and degradable properties, it can achieve the effect of synergistically promoting cell growth and angiogenesis by combining with BG, and can be rapidly degraded, thereby solving the problem that the engineered tissue materials in the prior art lack the ability to promote tissue reconstruction and positively regulate cells to shorten the repair cycle, and their own degradation cycle is relatively long;

[0059] 1. Another fiber membrane of the present invention is added with a combination of nano-cerium oxide and poloxamer. Nano-cerium oxide can provide antioxidant protection and reduce postoperative complications, while poloxamer can be used as a drug carrier to achieve local delivery of drugs in the repair area of ​​engineered tissue materials. This combination of materials can improve the effect of engineered tissue material repair, reduce the pain and recovery time of patients, and has a stronger positive regulatory effect on cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0061] Figure 1 A flow chart of a method for preparing a fiber membrane of the present invention;

[0062] Figure 2 SEM morphology of fiber membranes with different PPDO concentrations in Example 1 of the present invention

[0063] Figure 3 The SEM morphology of the fiber membranes at different drum speeds in Example 1 of the present invention;

[0064] Figure 4 The front, side and back SEM morphology images of PBDs of Example 2 of the present invention;

[0065] Figure 5 This is a front SEM morphology image of the PBDs of Example 2 of the present invention;

[0066] Figure 6 is a bar graph showing the fiber diameter distribution of PBDs of Example 2 of the present invention;

[0067] Figure 7 Schematic diagram of Si element mapping in the front microscopic morphology of PBDs of Example 2 of the present invention;

[0068] Figure 8 This is the XRD result diagram of PBDs of Example 2 of the present invention;

[0069] Fig. 9 This is a DSC result diagram of PBDs of Example 2 of the present invention;

[0070] Fig.10 Schematic diagram of the front side of PBDs of Example 2 of the present invention when a water drop falls and within 0.1s, 0.15s, and 0.2s after contact;

[0071] Fig.11 This is a schematic diagram of a water droplet falling on the back side of PBDs in Example 2 of the present invention;

[0072] Fig.12 This is a diagram showing the results of the PBDs tensile test of Example 2 of the present invention;

[0073] Fig.13 This is a front SEM morphology image of the PBDs during degradation in Example 2 of the present invention;

[0074] Fig.14 is a line graph of Si release during degradation of PBDs in Example 2 of the present invention;

[0075] Fig.15 It is a line graph of pH change during the degradation of PBDs in Example 2 of the present invention;

[0076] Fig.16 It is a line graph of mass change during degradation of PBDs in Example 2 of the present invention;

[0077] Fig.17 This is a cell live-death staining of PBDs in Example 2 of the present invention, and a comparison chart of DAPI and rhodamine-labeled phalloidin staining of cells on day 3;

[0078] Fig.18 This is a graph showing the cell CCK-8 results of the PBDs of Example 2 of the present invention;

[0079] Fig.19 This is a graph showing the hemolysis test results of PBDs in Example 2 of the present invention;

[0080] Fig. 20 This is a graph showing angiogenesis of PBDs in Example 2 of the present invention within 4 hours;

[0081] Fig.21 A histogram of the number of tubule connections in the angiogenesis image of PBDs according to Example 2 of the present invention;

[0082] Fig. 22 A histogram of the total area of ​​tubules in the angiogenesis image of PBDs according to Example 2 of the present invention;

[0083] Fig.23 A histogram of the total length of tubules in the angiogenesis image of PBDs according to Example 2 of the present invention;

[0084] Fig.24 TEM microscopic morphology of CNPs of Example 3 of the present invention;

[0085] Fig.25 This is the XRD result diagram of CNPs of Example 3 of the present invention;

[0086] Fig.26 This is the XPS result diagram of CNPs of Example 3 of the present invention;

[0087] Fig. 27 This is a CCK-8 result diagram of CNPs of Example 3 of the present invention;

[0088] Fig.28 This is a cell live-death staining of CNPs in Example 3 of the present invention, and a comparison chart of DAPI and rhodamine-labeled phalloidin staining of cells on day 3;

[0089] Fig.29 The front SEM morphology and Ce and Si element mapping distribution diagram of CBPPs of Example 4 of the present invention;

[0090] Fig.30 This is a graph showing the cell CCK-8 results of CBPPs in Example 4 of the present invention;

[0091] Fig.31 This is a cell live-death staining of CBPPs in Example 4 of the present invention, and a comparison chart of DAPI and rhodamine-labeled phalloidin staining of cells at day 3;

[0092] Fig.32 This is a diagram showing the hemolysis test results of CBPPs in Example 4 of the present invention;

[0093] Fig.33 This is a graph showing the angiogenesis experiment of CBPPs in Example 4 of the present invention within 4 hours. DETAILED DESCRIPTION

[0094] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0095] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention.

[0096] Polydioxanone (PPDO) is a biomedical polymer material of the aliphatic polyester class that can be degraded in the human body. It has good flexibility and excellent tensile strength, as well as excellent biocompatibility, mechanical properties and degradation rate. PPDO has gradually replaced materials such as polylactic acid (PLA) and polyglycolic acid (PGA) and has become one of the main materials for surgical sutures. It is a very suitable artificial material for in vivo implants. The advantages of PPDO materials are: (1) Compared with the existing fiber membrane materials polycaprolactone (PCL) and polylactic acid (PLLA), PPDO materials have good flexibility and excellent tensile strength and degradation cycle, making them suitable for medical applications that withstand tension and avoiding the need for secondary surgery for removal. The degradation products are ultimately harmless to the human body. (2) Compared with the existing fiber membrane materials polyglycolic acid (PGA) and polyurethane (PU), PPDO materials have good biocompatibility and mechanical properties, and can reduce rejection and inflammatory reactions with human tissues. (3) PPDO exhibits good stability during heat treatment, making it easy to process and shape. It can be chemically or physically modified to give it additional functions, such as sustained drug release and antibacterial properties.

[0097] The following is a fiber membrane with polydioxanone as the base material and a preparation method thereof provided by the present invention. The fiber membrane with polydioxanone as the base material mainly comprises: an outer dense layer of PPDO material, and an inner layer of PPDO material formed by electrostatic spinning on the outer dense layer. Among them, electrostatic spinning is a special fiber manufacturing process, which uses a polymer solution or melt to perform jet spinning in a strong electric field. The principle is that under the action of the electric field, the droplet at the needle tip will change from a sphere to a cone (i.e., a "Taylor cone"), and extend from the tip of the cone to obtain fiber filaments. Electrospinning can produce polymer filaments with nanometer-scale diameters. In the biomedical field, the diameter of nanofibers is smaller than that of cells, which can simulate the structure and biological function of natural extracellular matrix; and most human tissues and organs are similar to nanofibers in form and structure, which provides the possibility for nanofibers to be used for tissue and organ repair. At the same time, some electrospun raw materials have good biocompatibility and degradability, can be used as carriers to enter the human body, and are easily absorbed; in addition, electrospun nanofibers have excellent properties such as large specific surface area and porosity. Therefore, electrospun nanofibers have attracted continuous attention from researchers in the biomedical field and have been well applied in drug controlled release, wound repair, biological tissue engineering, etc.

[0098] In the process of preparing the fiber membrane with polydioxanone as the base material of the present invention, PPDO solution a is first prepared, and the PPDO base membrane is prepared using the PPDO solution a; then PPDO electrospinning solution c is prepared; and then the PPDO electrospinning solution c is used to perform electrostatic spinning on the PPDO base membrane to prepare a PPDO / BG double-layer fiber membrane. The specific preparation method of the fiber membrane with polydioxanone as the base material is as follows:

[0099] S10. Preparation of PPDO basement membrane: Mix PPDO and hexafluoroisopropanol, seal and avoid light, stir at room temperature, so that PPDO is completely dissolved in hexafluoroisopropanol, and place in a vacuum defoamer to remove bubbles in the mixture to obtain pure PPDO solution a. Then, pour the pure PPDO solution a into the glass dish three times at intervals, and gently apply it with an applicator after each pouring to ensure that its surface is uniform. During the interval, strictly ensure that PPDO solution a is in a vacuum state to prevent oxidative degradation of PPDO. After three times of film laying, put it into a constant temperature vacuum drying oven and dry it in a vacuum environment to obtain a uniform PPDO basement membrane.

[0100] S20. Prepare PPDO electrospinning solution c: Mix PPDO and hexafluoroisopropanol, seal and protect from light, and stir at room temperature to allow PPDO to completely dissolve in hexafluoroisopropanol. Place the mixture in a vacuum debubbler to remove bubbles in the mixture to obtain electrospinning solution c.

[0101] It should be noted that there is no fixed order between step S10 and step S20 in the present invention, and the two steps can be performed simultaneously or sequentially in different time periods.

[0102] S30. Electrospinning: Add the prepared PPDO electrospinning solution c into the electrospinning liquid syringe to remove bubbles. Use an electrospinning instrument (NANON-01A MECC, Japan) and a flat receiver. Attach the conductive tin foil to the flat receiver and ground the receiver. Fix the PPDO substrate membrane on the conductive tin foil. Keep the distance between the electrospinning needle and the receiver to perform multiple electrospinning solutions. After spinning, remove the fiber membrane from the conductive tin foil to obtain a PPDO / BG double-layer fiber membrane.

[0103] In a fiber membrane of the present invention, on the one hand, PPDO is used as the outer dense layer to prevent the penetration of cerebrospinal fluid in the skull; on the other hand, PPDO has good cell compatibility and degradable properties, so as to improve the cell compatibility and rapid degradation performance of the fiber membrane, thereby solving the problem of poor cell compatibility of fiber membrane substitutes in the prior art and a long degradation cycle of the fiber membrane substitutes.

[0104] At the same time, bioactive glass (BG) is a type of silicate material with biological activity, which is composed of SiO2, Na2O, CaO and P2O5 in a specific ratio. The Si ions produced by the reaction on the surface of BG can significantly affect cell behavior, including stimulating angiogenesis of endothelial cells and promoting fibroblasts to secrete vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF). Studies in the prior art show that when the Si concentration released in vivo by materials added with bioglass is around 1μg / mL, the effect on stimulating cells to secrete growth factors is the best, and the effect will change significantly with slight changes in Si concentration.

[0105] Since PPDO has good biocompatibility and BG at a specific concentration has the ability to positively regulate cell behavior, and the brain relies on precise regulation of ions to achieve its complex physiological functions, ions are crucial for meningeal defect repair, synaptic function, and the stability of the entire brain environment. The present invention also proposes a fiber membrane based on polydioxanone, the main structure of which is an artificial double-layer structure film based on PPDO and BG that imitates natural dura mater. The purpose of positively regulating intracranial cell behavior can be achieved by finely changing the Si concentration contained in the double-layer structure film.

[0106] The following is another fiber membrane with polydioxanone as the base material and its preparation method provided by the present invention. The fiber membrane with polydioxanone as the base material mainly comprises: an outer dense layer of PPDO material, and an inner layer of PPDO material formed by electrospinning on the outer dense layer and incorporating a certain concentration of BG.

[0107] In the preparation process of the fiber membrane based on polydioxanone of the present invention, PPDO solution a is first prepared, and the PPDO basement membrane is prepared using the PPDO solution a; then PPDO solution b is prepared, and BG suspension is added to prepare PPDO electrospinning solution c containing bioglass; then, electrostatic spinning is performed on the PPDO basement membrane using the PPDO electrospinning solution c containing bioglass to prepare a PPDO / BG double-layer artificial dura mater. The specific preparation method of the fiber membrane based on polydioxanone is as follows:

[0108] S10. Preparation of PPDO basement membrane: Mix PPDO and hexafluoroisopropanol, seal and avoid light, stir at room temperature, so that PPDO is completely dissolved in hexafluoroisopropanol, and place in a vacuum defoamer to remove bubbles in the mixture to obtain pure PPDO solution a. Then, pour the pure PPDO solution a into the glass dish three times at intervals, and gently apply it with an applicator after each pouring to ensure that its surface is uniform. During the interval, strictly ensure that PPDO solution a is in a vacuum state to prevent oxidative degradation of PPDO. After three times of film laying, put it into a constant temperature vacuum drying oven and dry it in a vacuum environment to obtain a uniform PPDO basement membrane.

[0109] S20. Preparation of PPDO electrospinning solution c containing bioglass: PPDO is mixed with hexafluoroisopropanol, sealed and light-proof, and stirred at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, and the mixture is placed in a vacuum debubbler to remove bubbles in the mixture to obtain a pure PPDO solution b. Then, excess BG powder is mixed with deionized water, ultrasonically shaken to mix evenly, centrifuged to obtain the supernatant, and then a quantitative BG suspension is added to the pure PPDO solution b to obtain a PPDO electrospinning solution c containing bioglass.

[0110] It should be noted that there is no fixed order between step S10 and step S20 in the present invention, and the two steps can be performed simultaneously or sequentially in different time periods.

[0111] S30. Electrospinning: Add the prepared PPDO electrospinning solution c containing bioglass into the electrospinning liquid syringe to remove bubbles. Use an electrospinning instrument (NANON-01A MECC, Japan) and a flat receiver. Attach the conductive tin foil to the flat receiver and ground the receiver. Fix the PPDO basement membrane on the conductive tin foil. Keep the distance between the electrospinning needle and the receiver to perform electrospinning solution spinning multiple times. After spinning, remove the fiber membrane from the conductive tin foil to obtain the PPDO / BG double-layer artificial dura mater.

[0112] In another fiber membrane of the present invention, on the one hand, PPDO is used as the outer dense layer to prevent the penetration of intracranial cerebrospinal fluid; on the other hand, PPDO is added with a certain concentration of BG, and the inner layer is prepared by electrospinning technology. Since electrospinning can produce a structure similar to the extracellular matrix (ECM), and PPDO has good cell compatibility and degradable properties, it can achieve the effect of synergistically promoting cell growth and angiogenesis by combining with BG, and can be rapidly degraded, thereby solving the problem that artificial dura mater substitutes in the prior art lack the ability to promote tissue reconstruction and positively regulate cells to shorten the repair cycle, and their own degradation cycle is relatively long.

[0113] In addition, the present invention further adopts the scheme of adding nano cerium oxide (chemical formula CeO2, referred to as CNP) and poloxamer, thereby providing another fiber membrane with polydioxanone as the substrate. Among them, nano cerium oxide has been widely studied due to its unique physicochemical properties, such as redox ability, catalytic activity and biocompatibility. These characteristics of nano cerium oxide make it have potential application value in the biomedical field, especially in drug carriers and tissue engineering. For example, nano cerium oxide can be used as an antioxidant material to protect cells from oxidative stress, and can also be used as a drug carrier to improve the delivery efficiency and therapeutic effect of drugs. Poloxamer is a non-ionic surfactant, which is usually used as a stabilizer and carrier in drug delivery systems. It can form a thermoreversible gel, which makes it very useful in controlling drug release. Poloxamer has good biocompatibility and can be degraded by organisms, so it has been widely used in drug delivery systems.

[0114] The following is another fiber membrane based on polydioxanone and a preparation method thereof provided by the present invention. The fiber membrane based on polydioxanone mainly comprises: an outer dense layer of PPDO material, and an inner layer of PPDO-poloxamer hydrogel in which BG and CNP are incorporated into the PPDO material formed by electrospinning on the outer dense layer.

[0115] In another process of preparing a fiber membrane based on polydioxanone, PPDO solution a is first prepared, and PPDO solution a is used to prepare a PPDO basement membrane; then PPDO solution b is prepared, and BG suspension is added to prepare PPDO electrospinning solution c containing bioglass; nano-cerium oxide and poloxamer are used to prepare electrospinning solution d; then electrospinning solution c and electrospinning solution d are used to simultaneously perform electrospinning on the PPDO basement membrane to prepare a double-layer artificial dura mater. The specific preparation method of the fiber membrane based on polydioxanone is as follows:

[0116] S10. Preparation of PPDO basement membrane: Mix PPDO and hexafluoroisopropanol, seal and avoid light, stir at room temperature, so that PPDO is completely dissolved in hexafluoroisopropanol, and place in a vacuum defoamer to remove bubbles in the mixture to obtain pure PPDO solution a. Then, pour the pure PPDO solution a into the glass dish three times at intervals, and gently apply it with an applicator after each pouring to ensure that its surface is uniform. During the interval, strictly ensure that PPDO solution a is in a vacuum state to prevent oxidative degradation of PPDO. After three times of film laying, put it into a constant temperature vacuum drying oven and dry it in a vacuum environment to obtain a uniform PPDO basement membrane.

[0117] S20. Prepare electrospinning solution c: Mix PPDO and hexafluoroisopropanol, seal and avoid light, stir at room temperature, so that PPDO is completely dissolved in hexafluoroisopropanol, and place in a vacuum debubbler to remove bubbles in the mixed solution to obtain a pure PPDO solution b. Then, mix excess BG powder with deionized water, ultrasonically vibrate to mix them evenly, centrifuge to obtain the supernatant, and then take a certain amount of BG suspension and add it to the pure PPDO solution b to obtain an electrospinning solution c containing bioglass.

[0118] S22. Prepare electrospinning solution d: Mix the CNPs cluster formed by CNP nanoparticles with hexafluoroisopropanol, seal and protect from light, and perform ultrasonic treatment at room temperature to make nano-cerium oxide evenly dispersed in hexafluoroisopropanol. Then add poloxamer, seal and protect from light, and perform stirring at room temperature to make poloxamer completely dissolved in hexafluoroisopropanol to prepare electrospinning solution d.

[0119] It should be noted that there is no definite order among preparing the PPDO substrate membrane in S10, preparing the electrospinning solution c in S20, and preparing the electrospinning solution d in S22 in the present invention. The three steps can be performed simultaneously or sequentially in different time periods.

[0120] S30. Electrospinning: Double-head synchronous electrospinning technology was used. Electrospinning solution c and electrospinning solution d were injected using different syringes. A roller receiver was used. The conductive tin foil was attached to the roller receiver and the receiver was grounded. The electrospinning needle was kept at a distance from the receiver. Electrospinning solution c and electrospinning solution d were spun synchronously. After spinning, the fiber membrane was removed from the conductive tin foil to obtain an electrospun double-layer artificial dura mater of PPDO-poloxamer hydrogel containing BG and CNP.

[0121] In another fiber membrane based on polydioxanone of the present invention, the combination of nano-cerium oxide and poloxamer brings some unique advantages. Among them, nano-cerium oxide can provide antioxidant protection and reduce postoperative complications, while poloxamer can be used as a drug carrier to achieve local delivery of drugs in the dura mater repair area. This combination of materials can improve the effect of dura mater repair and reduce the patient's pain and recovery time.

[0122] It should be noted that the fiber membrane based on polydioxanone of the present invention can be used not only for repairing artificial dura mater, but also as a tissue engineering scaffold and artificial tissue membrane in other parts of the body.

[0123] In order to specifically illustrate the beneficial effects of the present invention, specific embodiments and corresponding experimental results are provided below.

[0124] Example 1

[0125] This embodiment provides a PPDO fiber membrane (including multiple groups) prepared by electrospinning and a preparation method thereof. The fiber membrane with polydioxanone as the base material mainly comprises: an outer dense layer of PPDO material, and an inner layer of PPDO material formed by electrospinning on the outer dense layer. The preparation process of the fiber membrane with polydioxanone as the base material is as follows:

[0126] S10. Preparation of PPDO basement membrane:

[0127] 1.8g PPDO was mixed with 30mL hexafluoroisopropanol, sealed and light-proof, and stirred at room temperature for 4h. In one or more other embodiments, it can also be stirred for 4-8h to make PPDO completely dissolved in hexafluoroisopropanol, and placed in a vacuum defoamer for 0.5h to remove bubbles in the mixture to obtain 30mL of pure PPDO solution a with a concentration of 6g / mL. The pure PPDO solution a was divided into three times, 10mL each time, and poured into a glass dish with a radius of 10cm at an interval of 0.5h. After each pouring, it was gently spread with an applicator to ensure that its surface was uniform. In one or more other embodiments, it can also be poured at an interval of 0.5-1.5h. During the interval, the PPDO solution a was strictly kept in a vacuum state to prevent PPDO from oxidative degradation. After three times of film laying, it was placed in a 37°C constant temperature vacuum drying oven and dried in a vacuum environment for 36h to obtain a uniform PPDO base film. In one or more other embodiments, it can also be dried for 24-72h, in order to obtain a uniform PPDO base film after drying.

[0128] S20. Preparation of PPDO electrospinning solution c:

[0129] 0.6 g, 0.7 g, 0.8 g, 0.9 g, 1.0 g, and 1.1 g of PPDO were mixed with 10 mL of hexafluoroisopropanol, respectively, sealed and protected from light, and stirred at room temperature for 4 h. In one or more other embodiments, stirring can also be performed for 4 to 8 h, so that PPDO is completely dissolved in hexafluoroisopropanol. The mixture was placed in a vacuum defoamer for 0.5 h to remove bubbles in the mixture, and 10 mL of PPDO electrospinning solution c with concentrations of 0.06 g / mL, 0.07 g / mL, 0.08 g / mL, 0.09 g / mL, 0.1 g / mL, and 0.11 g / mL were obtained.

[0130] S30. Preparation of oriented PPDO electrospinning fiber membrane:

[0131] The prepared electrospinning solution c was added to a 5 mL electrospinning liquid syringe with a diameter of 12.5 mm, and bubbles were removed to ensure uniform solution ejection during electrospinning. Using an electrospinning instrument (NANON-01A MECC, Japan), the voltage was adjusted to 18 kV, the syringe propulsion speed was 5 mL / h, a roller receiver was used, the conductive tin foil was attached to the roller receiver and the receiver was grounded, the distance between the electrospinning needle and the receiver was 50 mm, the needle moved left and right at a speed of 100 mm / sec, 10 mL of electrospinning solution c was spun each time, and the fiber membrane was removed from the conductive tin foil after spinning to obtain multiple groups of PPDO electrospinning fiber membranes with different orientation degrees and fiber diameters. It should be noted that in one or more other embodiments, the voltage is controlled within the range of 10~30kV, the syringe propulsion speed is controlled within the range of 0.1~5mL / h, the distance between the electrospinning needle and the receiver is controlled within the range of 50~150mm, and the left and right movement speed of the needle is suitable for being controlled within the range of 25~100mm / sec, and the receiver rotation speed is controlled within the range of 0-5000 rpm.

[0132] Example 1 Beneficial Effect Analysis

[0133] See also Figure 2 , Figure 3 In order to test the beneficial effects of the present invention, the surface morphology structure of the PPDO double-layer fiber membrane of Example 1 was detected. Among them, the morphology and microstructure of the front side of the dried sample of Example 1 were tested. The fiber was cut and gold-sprayed for cross-sectional imaging. After obtaining the SEM image, the fiber diameter of each sample was counted.

[0134] The front structure of the PPDO electrospun fiber membrane in Example 1 was observed using a scanning electron microscope. Figure 2 , Figure 3 As shown in: when the PPDO concentration of the electrospinning solution c is in the range of 0.06 g / mL~0.1 g / mL and the drum speed of the electrospinning instrument is in the range of 900 rpm~1200 rpm, the electrospinning inner layer can obtain a relatively uniform and dense structure.

[0135] Example 2

[0136] This embodiment provides a fiber membrane (including six groups) based on polydioxanone and a preparation method thereof. The fiber membrane based on polydioxanone mainly comprises: an outer dense layer of PPDO material, and an inner layer of PPDO material formed by electrospinning on the outer dense layer and incorporating a certain concentration of BG. The preparation process of the fiber membrane based on polydioxanone is as follows:

[0137] S10. Preparation of PPDO basement membrane:

[0138] 1.8g PPDO was mixed with 30mL hexafluoroisopropanol, sealed and light-proof, and stirred at room temperature for 4h. In one or more other embodiments, it can also be stirred for 4~8h, in order to make PPDO completely dissolved in hexafluoroisopropanol, and then placed in a vacuum defoamer for 0.5h to remove bubbles in the mixture to obtain 30mL of pure PPDO solution a with a concentration of 6g / mL. The pure PPDO solution a was divided into three times, 10mL each time, and poured into a glass dish with a radius of 10cm at an interval of 0.5h. After each pouring, it was gently spread with an applicator to ensure that its surface was uniform. In one or more other embodiments, it can also be poured at an interval of 0.5~1.5h. During the interval, the PPDO solution a was strictly kept in a vacuum state to prevent PPDO from oxidative degradation. After three times of film laying, it was placed in a 37°C constant temperature vacuum drying oven and dried in a vacuum environment for 36h. In one or more other embodiments, it can also be dried for 24~72h, in order to obtain a uniform PPDO basement membrane after drying.

[0139] S20. Preparation of PPDO electrospinning solution c containing bioglass:

[0140] 0.6g PPDO was mixed with 10mL hexafluoroisopropanol, sealed and light-proof, and stirred at room temperature for 4h to make PPDO completely dissolved in hexafluoroisopropanol. In one or more other embodiments, stirring can also be performed for 2-8h, because the electrospinning solution will be stirred again after adding BG powder, so the first stirring time can be appropriately shortened. Then place it in a vacuum defoamer for 0.5h to remove bubbles in the mixed solution, and obtain 10mL PPDO solution b with a concentration of 0.06g / mL. Excess BG powder was mixed with deionized water, ultrasonically shaken for 1h to mix it evenly, centrifuged at 2000rpm for 5min, and in one or more other embodiments, it can also be centrifuged at 2000-4000rpm, and then the supernatant was taken and the silicon concentration in the BG suspension was quantitatively determined by ICP-OES. Then, a certain amount of BG suspension was added to PPDO solution b so that the silicon concentrations in the mixed electrospinning solutions c were 0.5 mg / L, 1 mg / L, 1.5 mg / L, 2 mg / L, 10 mg / L, and 50 mg / L, respectively, to obtain six groups of electrospinning solutions c.

[0141] S30. Electrospinning:

[0142] The six groups of electrospinning solutions c were added to a 5 mL electrospinning liquid syringe with a diameter of 12.5 mm, and bubbles were removed. Using an electrospinning instrument (NANON-01A MECC, Japan), the voltage was adjusted to 14 kV, the syringe propulsion speed was 3 mL / h, a flat receiver was used, the conductive tin foil was attached to the flat receiver and the receiver was grounded, the PPDO base film in step S10 was fixed on the conductive tin foil, the distance between the electrospinning needle and the receiver was 120 mm, the needle moved left and right at a speed of 50 mm / sec, 10 mL of electrospinning solution c was spun each time, and the fiber membrane was removed from the conductive tin foil after spinning. Six groups of electrospinning solutions c were used to obtain six PPDO / BG double-layer artificial dura maters with different BG contents, which were named PBD-1, PBD-2, PBD-3, PBD-4, PBD-5, and PBD-6 as six groups for comparative experiments. It should be noted that in one or more other embodiments, the voltage is controlled within the range of 10~30kV, the syringe propulsion speed is controlled within the range of 0.1~5mL / h, the distance between the electrospinning needle and the receiver is controlled within the range of 50~150mm, and the left and right movement speed of the needle is suitable for being controlled within the range of 25~100mm / sec, and the receiver rotation speed is controlled within the range of 0-5000 rpm.

[0143] Example 2 Beneficial Effect Analysis

[0144] See also Figure 4-Figure 23 In order to test the beneficial effects of the present invention, the physicochemical properties, mechanical properties, water absorption rate and in vitro degradation properties of the PPDO / BG double-layer artificial dura mater of Example 2, as well as the effect of the BG content of the dura mater on cell proliferation, cell morphology and the cell compatibility of the material were tested.

[0145] 1. Analysis of physical and chemical properties

[0146] (1) Surface morphology and structure analysis

[0147] The morphology and microstructure of the front and back sides and cross-section of the dried sample of Example 2 were tested, and the element distribution and relative abundance on the surface of the sample of Example 2 were tested using EDS. The cross-sectional imaging was performed by cutting the fiber and spraying gold. After obtaining the SEM image, the fiber diameter of each sample was counted.

[0148] Among them, the front, back and side structures observed by scanning electron microscope are as follows Figure 4As shown: The front SEM image of PBDs is a classic isotropic electrospinning structure. The grid is evenly distributed at different magnifications, and there is no obvious beading, indicating that the PPDO / BG double-layer material (PBD) has the performance of traditional electrospinning films, especially the ability to mimic the extracellular matrix ECM. The reverse SEM image shows the melt layer, which has a dense and uniform structure without pores, indicating that the preparation process can ensure the uniformity of the reverse side. The side SEM image shows that the dense melt layer and the electrospinning layer are tightly combined without fracture, and the double-layer structure exists stably. At the same time, Figure 5 , Figure 6 As shown in Figure 2, the fiber diameter distribution obtained by Image J shows that the fiber diameter of the spinning layer gradually decreases with the addition of bioglass, and no obvious inhomogeneous structure appears in all samples. Figure 7 The results of the mapping show that the bioglass BG with a specific Si content is evenly distributed in the PBD front spinning layer, and the Si content shown in the mapping increases with the increase of Si content, which is in line with the expected experimental results.

[0149] (2) XRD analysis

[0150] The dried PPDO raw material and PBDs dura mater were subjected to XRD test. The XRD spectrum of PBDs is as follows Figure 8 As shown. The experimental results show that two characteristic peaks of PPDO raw materials and PBDs appear in PBDs near 2θ=21° and 2θ=23°. These are diffraction peaks exhibited by their similar crystal structures. The half-peak width becomes wider with the increase of the amount of bioglass added, and the relative peak height becomes lower with the increase of the amount of bioglass added. The results show that the crystallinity of PBDs with different contents of Si is decreasing. This is because bioglass is usually an amorphous or low-crystallinity material. When it is mixed into a polymer, especially when preparing fiber films by electrospinning, the non-crystalline nature of bioglass may affect the crystallinity of the overall material. The amorphous nature of bioglass can inhibit the crystallization of polymer molecules, making the overall material more amorphous. At the same time, after adding BG, the freedom of the long and short chains of ppdo is reduced from a physical perspective, thereby changing the crystallization properties.

[0151] (3) DSC analysis

[0152] DSC was used to characterize the thermodynamic properties of PBDs. The melting temperature (Tm) and melting enthalpy ( ), the melting enthalpy of 100% crystalline PPDO It is 141.18 J / g. The crystallinity is calculated as follows:

[0153]

[0154] The DSC results of PBDs are as follows Fig. 9 As shown in Figure 2, the peak positions of all samples are almost the same, and their melting temperatures (Tm) and melting enthalpies ( ) The difference is small. After calculation, the relative crystallinity results of PBDs are shown in the figure. The figure shows that with the addition of bioglass content, the overall relative crystallinity of PBDs shows a downward trend, which is basically consistent with the analysis results of XRD.

[0155] (II) Water contact angle analysis

[0156] The water contact angles on the front and back surfaces of PBDs were measured using an optical contact angle meter. Fig.10 , Fig.11 As shown, the experimental results show that the front side of PBD is super hydrophilic and is completely absorbed within 0.2s after the water drop falls. The dense layer on the back side is hydrophilic with a hydrophilic angle of 73°. The results are consistent with the properties of the PPDO material itself. Hydrophilicity can support cell adhesion, growth and differentiation, and reduce inflammation and foreign body reactions caused by the material in brain tissue.

[0157] (III) Mechanical properties analysis

[0158] The tensile properties of the sample PBDs were tested. The maximum tensile deformation displacement and maximum tensile stress at break of the sample were measured using an electronic universal testing machine. Fig.12 As shown, the results show that all sample groups meet the minimum maximum tensile stress at break (5Mpa) requirement for artificial dura mater. There is no significant difference in the maximum tensile deformation displacement and maximum tensile stress at break in the PBD-1~PBD-5 groups, and both have a significant downward trend in the PBD-6 group. This is because bioglass is usually a harder and more brittle material, while PPDO has relatively high toughness. The tensile strength of pure PPDO fiber membrane can reach 20Mpa. When a certain amount of bioglass is added, the rigidity of the material increases and the overall toughness of the material decreases, resulting in a step change in PBD-6 compared to other groups.

[0159] 4. In vitro degradation analysis

[0160] (1) In vitro degradation surface morphology analysis

[0161] PBS (Biosharp, US) buffer was used as simulated body fluid, and PBDs samples of different concentrations were weighed and immersed in the degradation solution. The samples were immersed and degraded at constant temperature for 1, 4, 7, 14, 21, and 28 days, and the solution was changed every 3 days. There were 3 control groups at each time point. Samples and degradation solutions were taken out at 6 time points for various characterizations.

[0162] During the in vitro degradation cycle, the morphological changes of PBD-1~PBD-6 groups are as follows Fig.13Revealed. The experimental results show that within the first 4 days, the degradation trends of the PBD-1~PBD-6 groups were roughly the same, and no significant morphological changes were observed. Under high- and low-magnification scanning electron microscope (SEM) observations, the fiber structure showed clear, uniform and linear electrospinning characteristics. At the end of the second week, the surface structure of the PBD-1~PBD-6 groups began to collapse, and the fibrous structure began to show slight bending. As the degradation process continued, by the fourth week, compared with the previous three cycles, the destruction of the surface structure was further aggravated, and most of the fibrous structures could no longer maintain their original straight shape. Under high-magnification SEM, the observed structure showed a "melting"-like state, and the deformation of the fiber structure was extremely significant. This series of changes reflects the gradual collapse of the material structure during the 28-day degradation process and the short degradation cycle.

[0163] (2) In vitro degradation weight loss rate, pH change, and Si release analysis

[0164] The pH of the degradation solution at each time point of in vitro degradation was measured, and the Si concentration in the degradation solution at a specific time point was measured using a spectrometer. The mass of the sample before the experiment was recorded as After the in vitro degradation sample is taken out, it is placed in a vacuum drying oven and the mass after drying to constant weight is recorded as The degradation rate is expressed as:

[0165]

[0166] Weight loss rate, pH change, and Si release of PBDs during PBS degradation for 4 weeks Fig.14 , Fig.15 , Fig.16 As shown. The experimental results show that in the first week, the weight loss rate of PBDs was close to zero. In the second week, the weight loss rate of all PBDs samples experienced a step-by-step increase, generally exceeding 5%. After four weeks of degradation, the weight loss rate of PBDs reached a peak, among which the PBD-6 group performed the most significantly (9.9%). The in vitro degradation weight loss of PBDs is mainly attributed to the hydrolysis of PPDO and the dissolution of low molecular weight components. The differences in weight loss rates observed among the various groups of PBDs samples can be attributed to the different fiber diameters during the electrospinning process. The fiber diameters of the PBD-1~PBD-6 groups gradually decreased. The refinement of the fiber diameter and the macroporous structure produced by electrospinning increased the contact area between water molecules and the fiber structure, thereby accelerating the degradation rate.

[0167] Regarding the change in pH, the trends of the samples in each group were basically the same. On the first day of degradation, the release of bioglass that was not wrapped inside the fiber but free between the PBDs fiber structure caused a short rise in pH. It was observed that the pH peak of the PBD-6 group at this stage could reach more than 8. As the degradation process continued, the pH degradation trends of each group gradually became consistent and stabilized between 6.8 and 7.0 within four weeks.

[0168] The results of silicon release are as follows Fig.14 As shown in , on the first day of the experiment, the silicon concentration rose briefly due to the release of free bioglass, and then remained stable for 4 to 7 days. Starting from the 14th day, the partial hydrolysis of PBDs led to the release of bioglass wrapped inside the PPDO fibers, causing the silicon concentration in the degradation solution to reach a peak on the 21st day. However, due to the slightly acidic environment brought about by the PPDO degradation product 2-hydroxyethoxyacetic acid, the pH value of the degradation solution did not increase significantly. By the fourth week, with the further collapse of the surface structure of PBDs, the internally wrapped bioglass was released, resulting in an increase in the overall silicon release. These experimental results are basically consistent with the trends of structural changes, pH changes, and weight loss rates observed by SEM, and together verify the systematic regularity of the degradation behavior of PBDs.

[0169] (V) Biocompatibility analysis

[0170] L929 cells (mouse fibroblasts) were selected for in vitro experiments and cultured in an incubator with MEM medium to a sufficient base number and healthy morphology. PBDs samples were immersed in the culture medium, placed in the incubator, and centrifuged to obtain sample extracts. Cells were seeded in 96-well plates, and the sample extracts were replaced after the cells were attached to the wall. Cell viability was evaluated on the 1st, 3rd, and 5th days of incubation. CCK-8 reagent was combined with cells and incubated in an incubator in the dark, and the absorbance was measured at 450 nm. In addition, cell viability was evaluated using a live / dead staining kit. Cells were seeded in 48-well plates, and the sample extracts were replaced after the cells were attached to the wall. After 3 days of incubation, the sample extracts were removed and washed. Then, the cells were fixed with paraformaldehyde and washed. Subsequently, the cells were permeabilized with Triton X-100 solution and washed. TRITC-labeled phalloidin staining solution was added to each well, incubated at room temperature in the dark, and then the staining solution was removed and washed. Finally, the cell nuclei were stained with DAPI solution, incubated at room temperature in the dark, and then the staining solution was removed and washed. An inverted microscope was used to observe the cell morphology and take photos.

[0171] (1) Cell activity

[0172] The cell compatibility of PBDs was evaluated using the L929 cell line. Fig.17As shown in the figure, the cell viability of PBD-1, PBD-2, PBD-3, and PBD-4 groups was >100% within 1, 3, and 5 days of culture, and significantly exceeded the control group on the 5th day, indicating that they can promote the proliferation of L929 cell lines. However, the cell viability of PBD-5 and PBD-6 groups was much lower than that of other groups during the culture period, with the cell viability of PBD-5 <60% and the cell viability of PBD-6 <20%, indicating that these two groups of materials have obvious cytotoxicity. This is because under the culture conditions of L929 cells with PBDs extract, 45S5 bioglass degrades and releases silicon ions, calcium ions, phosphate ions, etc. These ions have no obvious effect on cells at low doses or can positively promote cells. However, when the ion concentration exceeds a certain threshold, it will affect the stability of the intracellular and extracellular environment, leading to cell damage or death. Secondly, the degradation of 45S5 bioglass also leads to the release of alkaline substances. Excessively high alkaline environment may have negative regulation on the survival and normal function of cells, affecting the stability of cell membranes and the normal function of ion channels.

[0173] (2) Live / Dead

[0174] In order to further confirm the cytotoxicity of the samples, the Live / Dead assay was used to detect cell viability. Fig.17 , Fig.18 As shown, the experimental results showed that, except for the PBD-6 group, the cell density of the other groups also increased with the increase of culture days. The cell behaviors of the PBD-1 group and the control group were similar during the culture period. On the 3rd and 5th days, the cell density of the PBD-2, PBD-3, and PBD-4 groups was greater than that of the control group. However, the cell density of the PBD-5 group was low, and the number of live cells was less than that of the control group. Some cells in the PBD-6 group became spherical from the first day of culture, and the cell density did not change much on the 3rd and 5th days. The Live / Dead staining results were basically consistent with the CCK-8 test results.

[0175] (3) Cell morphology

[0176] DAPI and phalloidin solution were used to detect the effect of samples on cell morphology and further evaluate their cell compatibility. Fig.17 , Fig.18 As shown in the figure, the experimental results showed that the cells in the PBD-1, PBD-2, PBD-3, and PBD-4 groups maintained spindle and star shapes, and the cytoplasm and nucleus were clearly stained. However, the cells in the PBD-5 and PBD-6 groups were diffusely round and oval, with unclear cytoplasm staining and atrophic nuclei, indicating that PBD-5 and PBD-6 had high cytotoxicity, and the results were consistent with the CCK-8 and Live / Dead staining results.

[0177] 6. Blood compatibility analysis

[0178] Rabbit blood anticoagulated with sodium citrate was centrifuged to separate red blood cells and washed and diluted. Subsequently, PBDs were combined with red blood cell suspension, shaken and centrifuged, and the supernatant was placed in a 96-well plate. The absorbance of the supernatant was measured at 540 nm ( The absorbance of red blood cells treated with 0.1% Triton X-100 and PBS was respectively the positive control group ( ) and negative control group ( ), the absorbance of the material treated with PBS was the material control group ( ), and each sample was tested three times. The hemolysis rate of the sample was calculated as follows:

[0179]

[0180] like Fig.19 As shown, the experimental results show that the supernatants obtained by centrifugation of red blood cell suspension treated with PBDs sample solution are all transparent in color, but the quantitative absorbance analysis data show that the hemolysis rates of PBD-1~PBD-4 group materials are all lower than 5%, and the hemolysis rates of PBD-5~PBD-6 group are all higher than 5%. There are no statistical differences between the PBDs material groups, and there are significant statistical differences compared with the positive control group Triton X-100. The results indicate that the PBD-1~PBD-4 group materials are blood safe.

[0181] 7. In vitro angiogenesis

[0182] Due to the poor cell compatibility of PBD-5 and PBD-6 groups, they were no longer added to the experimental groups in subsequent experiments. HUVECs (human umbilical vein endothelial cells) were used to evaluate the angiogenic ability of PBDs. ECM medium (Endothelial Cell Medium) and endothelial cell growth supplement (ECGS) were used to resuscitate, passage and induce angiogenesis in HUVECs.

[0183] After rewarming, the HUVEC cell solution was placed in a centrifuge tube and ECM complete medium was added. A uniformly distributed cell suspension was obtained by centrifugation, adding medium and continuous blowing. The cell suspension was inoculated in a culture bottle and placed in a carbon dioxide incubator for culture, and fresh medium was replaced every 48 hours. When the cell fusion degree reached 70%, the passage operation was performed. The culture medium in the bottle was removed, the cells were washed, and then trypsin was added and shaken. When the cells in the culture bottle became round and white fog appeared on the bottle wall, complete medium was added to terminate the trypsin digestion. Then, the cell suspension was centrifuged, the culture medium was added and blown until the cells were evenly suspended, then inoculated in the culture bottle and placed in the incubator for culture. In addition, the entire 48-well culture plate bottom was evenly covered with matrix gel and placed in the incubator for culture. The HUVEC cells that have reached the requirements in the incubator are taken out, centrifuged and added with the sample extract soaked in ECM (the extract preparation method is the same as above), and the treated cell suspension is counted. After the counting is completed, 1.5×106 cells are added to each well of the culture plate covered with matrix gel and placed in the cell culture incubator for incubation. The cell morphology is observed and photographed using an inverted microscope. Each sample is repeated three times.

[0184] like Figure 20-22 As shown in the results of the angiogenesis experiment, compared with the control group, the extracts of PBD-1, PBD-2, PBD-3, and PBD-4 groups can significantly promote HUVEC in vitro angiogenesis, and with the increase of Si concentration, the length of the blood vessels, the number of connections, the number of formations, and the area of ​​the tubes all increase. This is because the Si ions in the bioglass can stimulate vascular endothelial cells to secrete growth factors, such as vascular endothelial growth factor (VEGF), etc., thereby promoting the proliferation and migration of vascular endothelial cells.

[0185] Based on the above experimental results, it can be seen that the PBD-1~PBD-4 groups have better effects, that is, when the silicon concentration in the electrospinning solution c is 0.5~2mg / L, the PBDs obtained meet the requirements of artificial dura mater in terms of microstructure morphology, crystallinity, tensile strength and hydrophilicity, and have a shorter degradation cycle, are better compatible with cells and blood, do not produce obvious cytotoxicity, and have the effect of promoting cell proliferation and migration. Through the combination of a shorter degradation cycle and the ability to promote cell tissue reconstruction, patients using the PBDs can recover faster.

[0186] Example 3

[0187] This example provides six kinds of nano-cerium oxide particles (CNPs) and their preparation methods, which are used to demonstrate the process of selecting suitable nano-particles to prepare another fiber membrane based on polydioxanone of the present invention. The preparation process of the six kinds of nano-cerium oxide particles is based on the existing technology, and the improved thermal decomposition method is used to synthesize nano-cerium oxide particles of different particle sizes and valence states. The specific process is as follows:

[0188] 10 mmol of cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O, 4.342 g) was placed in a three-hole round-bottom flask, and 150 mmol of 1-octadecene (39.455 g) and 30 mmol of oleylamine (8.025 g) were added. Then, the three-necked flask containing the weighed medicine was placed in an oil bath, and stirred continuously at 80°C and 200 rpm for 30 min to completely dissolve the cerium (III) nitrate hexahydrate in octadecene and oleylamine to form a brown-yellow liquid. Subsequently, the temperature was raised to 160°C and stirred continuously for 2 h to obtain CNP-1 group nanoparticles. In one or more other embodiments, the stirring time after heating was controlled to be 1.5 to 4 h.

[0189] Take the same 10 mmol cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O, 4.342 g), 150 mmol 1-octadecene (39.455 g), 30 mmol oleylamine (8.025 g), and add 400 mmol deionized water (7.2 g), repeat the steps of CNP-1 group, and obtain CNP-2 group nanoparticles.

[0190] The proportion of oleylamine was reduced to 15 mmol (4.025 g) and 10 mmol (2.675 g), respectively, and the steps of CNP-2 group were repeated to obtain CNP-3 and CNP-4 groups of nanoparticles.

[0191] The steps of group CNP-2 were repeated, and nitrogen was introduced as a protective gas throughout the preparation process to repeat the steps to obtain group CNP-5 nanoparticles.

[0192] The CNP-5 step was repeated, and the mixture was stirred at 80°C for 30 min under nitrogen protection, then heated to 190°C and stirred for 2 h to obtain CNP-6 group of nanoparticles.

[0193] The reaction solution of each group is taken out from the three-necked flask, cooled to room temperature and poured into a beaker. A large amount of a mixture of dichloromethane and ethanol 1:5 is added to disperse and precipitate the nanoparticles and allowed to stand for 24 hours. The CNPs group is obtained by centrifuging the sedimentation liquid at 4000 rpm with a low-speed centrifuge for 5 minutes. In one or more other embodiments, the standing time is controlled at 24 to 48 hours, and the centrifugal sedimentation liquid time is controlled at 5 to 30 minutes. Afterwards, anhydrous ethanol is used as a detergent and dispersant, the CNPs group is dispersed and then centrifuged to wash away the residual dichloromethane and other impurities, and repeated 5 times until the supernatant after centrifugation becomes transparent. Finally, the CNPs group is dispersed in anhydrous ethanol using an ultrasonic instrument to ensure that it is evenly dispersed and preserved.

[0194] Example 3 Analysis

[0195] See also Figure 24-28 In order to test the preparation method of CNPs suitable for use in another fiber membrane based on polydioxanone of the present invention, the physical and chemical properties, microscopic morphology, and cell compatibility of CNPs were tested.

[0196] 1. Analysis of particle size and physicochemical properties of CNPs

[0197] like Fig.24 TEM results showed that the particle sizes of the six groups of CNPs were 3.4±0.3 nm, 3.4±0.8 nm, 7.2±0.1 nm, 10±0.2 nm, 14±1.6 nm, and 8.7±0.7 nm, respectively, and the particle size distribution of each group was uniform. Fig.25 The results of XRD showed that the characteristic peaks of CNPs appeared at 28.46° (111), 33.10° (200), 47.40° (220), 56.22º (311), 59.01° (222), and 69.69° (400), which was consistent with the existing research results and proved the successful synthesis of CNPs. In addition, the XPS results of CNPs powder tested at C 1s (284.6 eV) showed that the work functions at 570.25 eV, 580.2 eV, 585.7 eV, 588.6 eV, 598.5 eV, and 604.5 eV were Ce4+, and the work functions at 583.1 eV, 587.1 eV, 601.6 eV, and 606.4 eV were Ce3+. The XPS data were peak fitted using avantage software to obtain the oxidation state ratio of CNPs. Fig.26 ,The results showed that the proportions of Ce3+ in the six groups of CNPs were 33.73%, 56.65%, 35.00%, 53.21%, 22.42% and 18.91%, respectively.

[0198] 2. Cytocompatibility analysis of CNPs

[0199] CNPs of different particle sizes and valences were mixed with MEM medium to keep the CNPs content in the medium at 0.1% and co-cultured with L929 cells. Fig. 27, CCK-8 results showed that the cell proliferation rates of all experimental groups were greater than 95% after 1, 3, and 5 days of co-culture. This indicates that CNPs in each group at 0.1% content were non-cytotoxic. After 1 day of incubation, the CNP-5 group had the best effect on promoting cell proliferation, followed by the CNP-2 group and the CNP-6 group. However, as the incubation time came to the 3rd and 5th days, the cell proliferation rates of the CNP-4 group, the CNP-5 group, and the CNP-6 group were lower than those of the control group. At this time, the CNP-2 group had the best effect on promoting cell proliferation. This indicates that after 1 day of co-culture with cells, the cells had a stronger toxic and side effect stress effect on the CNP-4 group, the CNP-5 group, and the CNP-6 group. As the culture time increased, the proliferation rates of the three groups decreased sharply and were all lower than those of the control group. The reason may be that the Ce3+ content of the CNP-5 group and the CNP-6 group was lower than that of the other groups, and their ability to regulate the content of reactive oxygen in the intracellular environment was weaker. Although the Ce3+ content in the CNP-4 group was high, its large particle size (14 nm±1.6 nm) affected the exchange of cells with external substances when co-cultured with cells, resulting in a strong toxic and side effect effect on the first day and a significant decrease in cell proliferation rate.

[0200] In addition, if Fig.28 As shown in the figure, the cell proliferation ability of CNPs was further evaluated by Live / Dead test. A large number of live cells were observed in all groups within 1, 3, and 5 days. After incubation for 3 and 5 days, it can be observed that the proportion of live cells in CNP-2 and CNP-3 groups is much greater than that in the control group and other experimental groups, and the proportion of live cells in CNP4-6 groups is significantly lower than that in the control group. This is basically consistent with the results of CCK-8 experiment, which once again shows that CNPs with a particle size of about 3.4±0.8 nm and a higher Ce3+ content are more conducive to promoting cell proliferation.

[0201] At the same time Fig.28 As shown, the morphology of L929 cells in all groups was normal, mostly spindle-shaped, with a small number of triangles and circles, and the pseudopodia were long and high in density. This shows that CNPs at a suitable concentration will not affect the cell morphology, and appropriate addition to the material can promote cell proliferation and play a positive regulatory role in tissue repair in specific areas.

[0202] Based on the above experiments, it can be seen that the CNPs prepared by the preparation method of CNP-2 group are more suitable for use in the artificial dura mater material of the present invention.

[0203] Example 4

[0204] This embodiment provides a fiber membrane based on polydioxanone (divided into four groups) and a preparation method thereof. The fiber membrane based on polydioxanone mainly comprises: an outer dense layer of PPDO material, and an inner layer of PPDO-poloxamer hydrogel formed by electrospinning PPDO material with BG and CNP on the outer dense layer. The preparation process of the fiber membrane based on polydioxanone is as follows:

[0205] S10. Preparation of PPDO basement membrane: 1.8g PPDO was mixed with 30mL hexafluoroisopropanol, sealed and light-proof, and stirred at room temperature for 4h. In one or more other embodiments, it can also be stirred for 4~8h. The purpose is to make PPDO completely dissolved in hexafluoroisopropanol, and then placed in a vacuum defoamer for 0.5h to remove bubbles in the mixed solution to obtain 30mL of pure PPDO solution a with a concentration of 6g / mL. The pure PPDO solution a was divided into three times, 10mL each time, and poured into a glass dish with a radius of 10cm at an interval of 0.5h. After each pouring, it was gently spread with an applicator to ensure that its surface was uniform. In one or more other embodiments, it can also be poured at an interval of 0.5~1.5h. During the interval, the PPDO solution a is strictly ensured to be in a vacuum state to prevent PPDO from oxidative degradation. After three times of film laying, it was placed in a 37℃ constant temperature vacuum drying oven and dried in a vacuum environment for 36h. In one or more other embodiments, it can also be dried for 24~72h. The purpose is to obtain a uniform PPDO basement membrane after drying.

[0206] S20. Preparation of PPDO electrospinning solution c containing bioglass: 2.4g PPDO was mixed with 30mL hexafluoroisopropanol, sealed and light-proof, and stirred at room temperature for 4h to make PPDO completely dissolved in hexafluoroisopropanol. In one or more other embodiments, stirring can also be performed for 2~8h. Because the electrospinning solution will be stirred again after adding BG powder, the first stirring time can be appropriately shortened. Then place it in a vacuum defoamer for 0.5h to remove bubbles in the mixed solution, and obtain 30mL of 0.08g / mL PPDO solution b. Excess 45s5-BG powder was mixed with deionized water, ultrasonically vibrated for 1h to mix it evenly, centrifuged at 2000rpm for 5min, and in one or more other embodiments, centrifuged at 2000~4000rpm, and the supernatant was taken. The silicon concentration in the BG suspension was quantitatively determined by icp-oes. A quantitative BG suspension was added to the pure PPDO solution b so that the silicon concentration in the mixed electrospinning solution c was 1.5mg / L, and the electrospinning solution c was obtained.

[0207] S22. Preparation of electrospinning solution d: 0.001g, 0.01g, 0.05g, 0.1g of CNPs of group 2 (CNP-2) of nano cerium oxide in Example 3 were mixed with 10mL of hexafluoroisopropanol, sealed and protected from light, and ultrasonicated at room temperature for 2h. In one or more other embodiments, the ultrasonic time is controlled at 1~4h, in order to make the nano cerium oxide uniformly dispersed in hexafluoroisopropanol. 3g of poloxamer was added to each group, sealed and protected from light, and stirred at room temperature for 2h. In one or more other embodiments, the stirring time was controlled at 2~8h, in order to make the poloxamer completely dissolved in hexafluoroisopropanol, and four groups of mixed electrospinning solutions d were obtained. The CNPs content of electrospinning solution d in each group was 0.01%, 0.1%, 0.5%, and 1%, respectively.

[0208] S30. Electrospinning: Using an electrospinning instrument (NANON-01A MECC, Japan), double-head synchronous electrospinning technology was used, the voltage was adjusted to 18 kV, the syringe propulsion speed of electrospinning solution c was 3 mL / h, and the syringe propulsion speed of electrospinning solution d was 1 mL / h. A roller receiver was used, and the conductive tin foil was attached to the roller receiver and the receiver was grounded. The distance between the electrospinning needle and the receiver was 50 mm, and the needle moved left and right at a speed of 25 mm / sec. The roller speed was set to 800 rpm. Each time, 30 mL of electrospinning solution c was spun, and 10 mL of electrospinning solution d was spun. After spinning, the fiber membrane was removed from the conductive tin foil. Four groups of mixed electrospinning solutions d with different CNPs group contents were used to obtain four groups of electrospun double-layer artificial dura maters (CBPPs) containing BG and CNP PPDO-poloxamer hydrogels, named CBPP-1, CBPP-2, CBPP-3 and CBPP-4, respectively, as four groups for comparative experiments. It should be noted that in one or more other embodiments, the voltage is controlled within the range of 15~25 kV, the syringe propulsion speed of the electrospinning solution c is controlled within the range of 1~5 mL / h, the syringe propulsion speed of the electrospinning solution d is controlled within the range of 0.1~2 mL / h, the distance between the electrospinning needle and the receiver is controlled within the range of 25~75 mm, the left and right movement speed of the needle is controlled within the range of 25~100 mm / sec, and the drum speed setting range is 200~800 rpm.

[0209] Example 4 Beneficial Effect Analysis

[0210] See also Figure 29-Figure 33 ,In order to test the beneficial effects of the present invention, the surface morphology structure of the electrospun double-layer artificial dura mater of PPDO-poloxamer hydrogel containing BG and CNPs, as well as the effects of CNPs and poloxamer on cell proliferation, cell morphology and the cell compatibility of the material were experimented.

[0211] 1. Surface morphology and structure analysis

[0212] The detection process is referred to Example 2. The hydrogel fiber membrane is observed using a scanning electron microscope. Fig.29 As shown: The surface of the electrospun double-layer material (CBPP) of PPDO-poloxamer hydrogel containing BG and CNP is a combination of isotropic electrospinning structure and hydrogel film structure. The poloxamer hydrogel is evenly distributed in the pores of the electrospinning fiber membrane. No beads appear in the electrospinning. The overall structure is dense, indicating that the preparation process is perfect. The results of mapping show that the bioglass BG with a specific Si element content is evenly distributed in the CBPP spinning fiber hydrogel layer. The Ce element shows that the Ce content shown in the mapping increases with the increase of CNP content, which is in line with the expected experimental results.

[0213] 2. Biocompatibility analysis

[0214] The experimental process is similar to that of Example 2.

[0215] Cell viability

[0216] The cell compatibility of CBPP was evaluated using the L929 cell line. Fig.30 As shown in the figure, the cell viability of CBPP-1, CBPP-2, and CBPP-3 groups exceeded 100% within 1 and 3 days of culture, among which CBPP-1 and CBPP-2 groups were much greater than the control group. On the 5th day, the CBPP-1 and CBPP-2 groups dropped to almost the same level as the control group, while the CBPP-3 and CBPP-4 groups were much lower than the control group. The overall results showed that BG bioglass and CNP nanoparticles can significantly promote cell proliferation within a reasonable concentration range, but excessive addition of CNP nanoparticles is cytotoxic.

[0217] Live / Dead

[0218] like Fig.31 As shown in the figure, the experimental results show that the cell density of all groups increases with the increase of culture days. On the 5th day, the cell density of CBPP-1 and CBPP-2 groups was much greater than that of the control group, and the cell behaviors of the other groups were similar to those of the control group during the culture period. Some cells in the CBPP-4 group became spherical from the first day of culture, and the cell density did not change much between the first day and the third day. The Live / Dead staining results were basically consistent with the CCK-8 test results, proving that an appropriate amount of BG-CNP can promote the proliferation of L929 cells.

[0219] Cell morphology

[0220] DAPI and phalloidin solution were used to detect the effect of samples on cell morphology and further evaluate their cell compatibility. Fig.31As shown in the figure, the cells in the CBPP-1 and CBPP-2 groups maintained a spindle shape, and the cytoplasm and nucleus were clearly stained. As the CNP content increased, the proportion of cells with diffuse round and oval shapes increased, the cytoplasm was not clearly stained, and the nucleus was atrophied. This was particularly evident in the CBPP-4 group, proving that this group had a higher cytotoxicity, which was basically consistent with the results of CCK-8 and Live / Dead staining.

[0221] 6. Blood compatibility analysis

[0222] The experimental process is as in Example 2. Fig.32 As shown, the experimental results show that the supernatants obtained by centrifugation of red blood cell suspension treated with CBPPs sample solution are all transparent in color, but the quantitative absorbance analysis data show that the hemolysis rates of CBPP-1~CBPP-4 group materials are all lower than 5%, there are no statistical differences between the CBPPs material groups, and there are significant statistical differences compared with the positive control group Triton X-100. The results indicate that the CBPP-1~CBPP-4 group materials are blood safe.

[0223] 7. In vitro angiogenesis

[0224] The experimental process is as in Example 2. Fig.33 As shown in the results of the angiogenesis experiment, compared with the control group, the extracts of the CBPP-1, CBPP-2, and CBPP-3 groups can significantly promote the in vitro angiogenesis of HUVEC, and with the increase of CNP concentration, the length of the blood vessels, the number of connections, the number of formations, and the area of ​​the tubes first increase and then decrease. When the concentration reaches a certain level, the CBPP-4 group can no longer promote the in vitro angiogenesis of HUVEC. This is due to the ability of CNP to regulate oxidative stress response and scavenge free radicals, which enables the CBPP-1, CBPP-2, and CBPP-3 groups to significantly positively regulate cells compared with the control group. However, the cytotoxicity caused by excessive concentrations affects the proliferation and differentiation of cells.

[0225] Based on the above experimental results, it can be seen that the CBPP-1~CBPP-2 groups have better effects, that is, when the CNP nanoparticle content in the electrospinning solution d is 0.01~0.1%, the obtained CBPPs can be well compatible with cells and blood, do not produce obvious cytotoxicity, and have a stronger positive regulatory effect on cells.

[0226] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a fiber membrane based on polydioxanone, characterized in that: The following steps are involved: S10. Mixing PPDO and an organic solvent to prepare a PPDO solution a, using the PPDO solution a to lay a film multiple times, and drying to obtain a PPDO basement membrane; S20. Preparing electrospinning solution c by mixing PPDO with an organic solvent; S30. On the PPDO substrate membrane, electrospinning is performed using the electrospinning solution c to obtain a fiber membrane with polydioxanone as the substrate; There is no fixed order between steps S10 and S20.

2. The method for preparing a fiber membrane based on polydioxanone as claimed in claim 1, characterized in that: The S20 includes: preparing a PPDO solution b by mixing PPDO with an organic solvent, and adding a BG suspension to the PPDO solution b to prepare a PPDO electrospinning solution c.

3. The method for preparing a fiber membrane based on polydioxanone as claimed in claim 2, characterized in that: The organic solvents used in S10 and S20 are both hexafluoroisopropanol, and the bubbles in the mixed PPDO solution a and PPDO solution b need to be removed.

4. The method for preparing a fiber membrane based on polydioxanone as claimed in claim 3, characterized in that: The S10 specifically includes: mixing PPDO and hexafluoroisopropanol, sealing and avoiding light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution a; pouring the pure PPDO solution a into a glass dish three times at intervals, and applying it with a coater after each pouring to ensure that the surface is uniform; after three times of film laying, placing the mixture in a constant temperature vacuum drying oven and drying in a vacuum environment to obtain a PPDO basement membrane.

5. The method for preparing a fiber membrane based on polydioxanone as claimed in claim 3, characterized in that: The S20 specifically includes: mixing PPDO with hexafluoroisopropanol, sealing and protecting from light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution b; mixing excess BG powder with deionized water, ultrasonically shaking to mix them evenly, centrifuging to obtain the supernatant, and then taking a certain amount of BG suspension and adding it to the pure PPDO solution b to obtain a PPDO electrospinning solution c.

6. The method for preparing a fiber membrane based on polydioxanone as claimed in claim 2, characterized in that: The S30 specifically includes: adding the electrospinning solution c into an electrospinning liquid syringe to remove bubbles; performing electrospinning multiple times using an electrospinning instrument to obtain a fiber membrane with polydioxanone as a substrate; Among them, the spinning voltage is controlled at 10~30kV, the syringe propulsion speed is controlled at 0.1~5mL / h, the distance between the electrospinning needle and the receiver is controlled at 50~150mm, and the left and right movement speed of the needle is suitable for being controlled at 25~100mm / sec, and the roller receiver speed is controlled at 0~5000 rpm.

7. The method for preparing a fiber membrane with polydioxanone as the base material according to any one of claims 1 to 6, characterized in that: The PPDO concentration of the electrospinning solution c prepared in S20 is 0.06 g / mL~0.10 g / mL.

8. The method for preparing a fiber membrane based on polydioxanone according to any one of claims 2 to 6, characterized in that: The silicon concentration of the electrospinning solution c prepared in S20 is 0.5 mg / L to 50 mg / L.

9. A fiber membrane with polydioxanone as the substrate, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Include: An outer dense layer of PPDO material; and An inner layer of PPDO material is formed by electrospinning on the outer dense layer.

10. A method for preparing a fiber membrane based on polydioxanone, characterized in that: The following steps are involved: S10. Mixing PPDO and an organic solvent to prepare a PPDO solution a, using the PPDO solution a to lay a film multiple times, and drying to obtain a PPDO basement membrane; S20. Mixing PPDO and an organic solvent to prepare a PPDO solution b, and adding a BG suspension to the PPDO solution b to prepare a PPDO electrospinning solution c; S22. CNPs were mixed with an organic solvent and poloxamer was added to prepare an electrospinning solution d; S30. On the PPDO substrate membrane, electrospinning solution c and electrospinning solution d are used to simultaneously perform electrospinning to obtain a fiber membrane based on polydioxanone; There is no fixed order among the steps S10, S20 and S22.

11. The method for preparing a fiber membrane based on polydioxanone according to claim 10, characterized in that: The organic solvents used in S10, S20 and S22 are all hexafluoroisopropanol, and the bubbles in the mixed PPDO solution a and PPDO solution b need to be removed.

12. The method for preparing a fiber membrane based on polydioxanone according to claim 11, characterized in that: The S10 specifically includes: mixing PPDO and hexafluoroisopropanol, sealing and avoiding light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution a; pouring the pure PPDO solution a into a glass dish three times at intervals, and applying it with an applicator after each pouring to ensure that the surface is uniform; after three times of film laying, placing the mixture in a constant temperature vacuum drying oven and drying in a vacuum environment to obtain a PPDO basement membrane.

13. The method for preparing a fiber membrane based on polydioxanone according to claim 11, characterized in that: The S20 specifically includes: mixing PPDO with hexafluoroisopropanol, sealing and protecting from light, stirring at room temperature to make PPDO completely dissolved in hexafluoroisopropanol, placing the mixture in a vacuum defoamer to remove bubbles in the mixture to obtain a pure PPDO solution b; mixing excess BG powder with deionized water, ultrasonically shaking to mix them evenly, centrifuging to obtain the supernatant, and then taking a certain amount of BG suspension and adding it to the pure PPDO solution b to obtain a PPDO electrospinning solution c.

14. The method for preparing a fiber membrane based on polydioxanone according to claim 11, characterized in that: The S22 specifically includes: mixing the CNPs group with hexafluoroisopropanol, sealing and protecting from light, and ultrasonically treating at room temperature to make the nano-cerium oxide uniformly dispersed in the hexafluoroisopropanol; adding poloxamer, sealing and protecting from light, and stirring at room temperature to make the poloxamer completely dissolved in the hexafluoroisopropanol, so as to prepare the electrospinning solution d.

15. The method for preparing a fiber membrane based on polydioxanone as claimed in claim 10, characterized in that: The S30 specifically includes: using double-head synchronous electrospinning technology, the electrospinning solution c and the electrospinning solution d are synchronously injected using different syringes; and using an electrospinning instrument to perform multiple electrospinning to obtain a fiber membrane with polydioxanone as the substrate.

16. The method for preparing a fiber membrane with polydioxanone as the base material according to any one of claims 10 to 15, characterized in that: The preparation method of the CNPs group used in S22 comprises: Place cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O) in a container, and add 1-octadecene, oleylamine and deionized water; place the container containing the weighed drugs in an oil bath, and continue to stir to completely dissolve cerium (III) nitrate hexahydrate in octadecene and oleylamine to form a brown-yellow liquid; then increase the temperature and continue to stir for 1.5-4 hours to obtain a reaction solution containing CNP nanoparticles; The reaction solution was taken out from the container, cooled to room temperature, and then a large amount of a mixture of dichloromethane and ethanol was added to disperse and precipitate the CNP nanoparticles, and the mixture was allowed to stand for 24 to 48 hours; the precipitated liquid was centrifuged in a low-speed centrifuge for 5 to 30 minutes to obtain CNPs clusters.

17. The method for preparing a fiber membrane with polydioxanone as the base material according to any one of claims 10 to 15, characterized in that: The CNPs content in the electrospinning solution d prepared in S22 is 0.01%~0.1%.

18. A fiber membrane based on polydioxanone, characterized in that: Prepared by the preparation method according to any one of claims 10 to 17, characterized in that it comprises: An outer dense layer of PPDO material; and The inner layer of PPDO-poloxamer hydrogel incorporating BG and CNP is formed by electrospinning on the outer dense layer.

Citation Information

Patent Citations

  • Fiber compact double-layered composite film, preparation method thereof and application of fiber compact double-layered composite film

    CN102525655A

  • Nano cerium oxide and preparation method thereof

    CN103449496A

  • Surface modification method for cerium nano-particles

    CN103551567A

  • Absorbable artificial dura mater having anti-infection function, preparation method and application thereof

    CN106943634A

  • Bone induction film and preparing method thereof

    CN108411495A